Does Inside Equal Outside? Relations Between Older Adults' Implicit and Explicit Aging Attitudes and Self-Esteem - Chen, Jing; Zheng, Kangjia; Xia, Weihai; Wang, Qi; Liao, Zongqing; Zheng, Yutong (Frontiers in Psychology, 2018)
Attitudes toward one's own aging and self-esteem are crucial variables in predicting older adults' physical and mental health and can significantly affect their will to live, cognitive judgement and acceptance of medical treatment. However, little is known about the relation between the implicit attitude toward one's own aging and implicit self-esteem. This research explored consistencies between implicit and explicit attitudes toward one's own aging and between implicit and explicit self-esteem and explored their relations in seventy older adults aged 60-91 years old using the word and picture versions of the Implicit Association Test and standardized scales. The results showed that a) the explicit and implicit attitudes toward one's own aging represented independent structures, and the implicit and explicit self-esteem also represented independent structures; b) subjects generally showed positive explicit attitudes toward their own aging and negative implicit attitudes toward their own aging while also showing high explicit self-esteem and relatively low implicit self-esteem; c) subjects' implicit attitudes toward their own aging and implicit self-esteem were positively correlated, and explicit attitudes toward their own aging and explicit self-esteem were also positively correlated. The more positive the subjects' explicit attitudes toward their own aging, the higher their explicit self-esteem levels were. The more negative their implicit attitudes toward their own aging, the higher their implicit self-esteem levels were. We concluded that older adults' explicit and implicit attitudes toward their own aging and self-esteem are independent structures; older adults' explicit and implicit attitudes toward their own aging have predictive effects on their explicit and implicit self-esteem in different directions, respectively.